2013
DOI: 10.1007/s12550-013-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium fungi and associated metabolites presence on grapes from Slovakia

Abstract: Toxinogenic Fusarium species were identified on grape berries from Slovak vineyards, and their toxic metabolites were analysed by HPLC-MS/MS. F. subglutinans, F. oxysporum, F. proliferatum, F. semitectum, F. solani, F. subglutinans, and F. verticillioides were found with varying frequency. F. oxysporum and F. proliferatum, cultured in vitro on Czapek yeast autolysate agar and yeast extract sucrose agar, produced beauvericin, in the range from 3,265 to 13,400 μg/kg, and fusaproliferin in high concentration, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Aurofusarin was the metabolite of interest in both G2 and G142, while the metabolite of interest produced by G24 was PC3. Aurofusarin is a mycotoxin and red pigment common in Fusarium species (Ezekiel et al , 2012; Soerensen et al , 2012; Mikusova et al , 2013). PC3 is an analog of pestalotin, which was first described as a product of an unidentified fungus in 1973 (Strunz et al , 1974); pestalotins synergistically augment the plant hormone gibberellin (Kimura et al , 1971; Kimura et al , 1977; Kirihata et al , 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Aurofusarin was the metabolite of interest in both G2 and G142, while the metabolite of interest produced by G24 was PC3. Aurofusarin is a mycotoxin and red pigment common in Fusarium species (Ezekiel et al , 2012; Soerensen et al , 2012; Mikusova et al , 2013). PC3 is an analog of pestalotin, which was first described as a product of an unidentified fungus in 1973 (Strunz et al , 1974); pestalotins synergistically augment the plant hormone gibberellin (Kimura et al , 1971; Kimura et al , 1977; Kirihata et al , 1996).…”
Section: Resultsmentioning
confidence: 99%
“…For example, beauvericin and enniatins frequently co-occur with other Fusarium derived metabolites in grains and food products. These include culmorin, DON and derivatives, equisetin, fumonisins, fusaproliferin, fusaric acid, fusareon-X, moniliformin, monocerin, nivalenol, T-2/HT-2 toxins and zearalenone and its derivatives [8,78,79,80,81,82,83,84,85,86]. Furthermore, in their analysis of 83 samples of feed and feed raw materials using a multi mycotoxin LC-MS/MS method, Streit et al [8], reported the co-occurrence of 69 different mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Within the fruit juice category, the regulated products, such as fruit juice, fruit juice from concentrate, concentrated fruit juice, water extracted fruit juice, dehydrated/powdered fruit juice, and fruit nectar, are defined based on their composition and manufacturing processes (Mihalev, Dinkova, Shikov, & Mollov, ). The bioactivity of fruit juices toward free radicals can also be used as a parameter for the definition of the quality of fruit juices, besides their safety (Mikusova, Ritieni, Santini, Juhasova, & Srobarova, ; Mikušová, Šrobárová, Sulyok, & Santini, ; Santini & Novellino, ).…”
Section: Antioxidant Properties Of Fruit‐based Juice: An Overviewmentioning
confidence: 99%
“…The bioactivity of fruit juices toward free radicals can also be used as a parameter for the definition of the quality of fruit juices, besides their safety (Mikusova, Ritieni, Santini, Juhasova, & Srobarova, 2010;Mikušová, Šrobárová, Sulyok, & Santini, 2013;Santini & Novellino, 2014).…”
Section: Significance Of Antioxidant Properties Of Foodsmentioning
confidence: 99%